Cryogenic energy storage powered by geothermal energy. (January 2019) - Cetin, Tugberk Hakan; Kanoglu, Mehmet; Yanikomer, Neslihan
Highlights: A cryogenic energy storage (CES) system powered by a geothermal power plant is proposed. The system consists of an air liquefaction unit, a single-flash geothermal plant, and a discharge unit. The CES unit has round trip efficiency of 46.7% and the overall efficiency of the plant is 24.4%. Effect of geothermal temperature on the system performance is investigated. Proposed system could be an effective solution for load shifting operations of geothermal power plants. Abstract: Geothermal energy is one of the promising alternatives of power generation suitable for energy storage applications for load shifting operations. Cryogenic energy storage (CES) is an attractive option for energy storage driven by geothermal power. In this study, thermodynamic assessment of a cryogenic energy storage unit integrated to a single-flash geothermal power plant is performed and the effect of geothermal source temperature on the system performance is investigated. Initially, a resource that can supply geothermal water at 180 °C at a rate of 100 kg/s is considered. Power generated from the geothermal plant during off-peak hours is used to produce and store liquefied air. This liquefied air is used to generate power during peak hours using the heat of geothermal water. Our analysis indicates that the liquefaction unit consumes 4304 kW power in order to liquefy air for a 6-h charging period. In the discharge mode, the CES unit can produce a net power output of 12, 049 kW for a 1-h operation. The flashing pressure is optimized at 255 kPa for which the total power output is 16, 100 kW. The round-trip efficiency of the CES unit is determined to be 46.7% while the overall efficiency of the integrated system is 24.4%.